1976
DOI: 10.1524/ract.1976.23.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects on 51Cr(III)-Doped Chromates and Other Oxy-Salts

Abstract: Radiation annealing studies in 51 Cr(III)-doped ammonium and potassium chromâtes were made by measuring the distribution of 51 Cr activity among 51 Cr(VI), 51 Cr(III)-monomer and 51 Cr(III)-dimer+polymer species following dissolution. Conversion of 51 Cr(III)-dopant atoms into 61 Cr(VI) forming species has been observed in both Chromate salts. In ammonium Chromate the dopant atoms were found also to give rise to DP forming species. These effects seemed to depend on the temperature of irradiation.The influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In each case, the observed ratio increases with a 16 hour thermal pulse at 300°C. These observations are consistent with conclusions from studies of 51 Cr(III)-doped Chromates [10][11][12][13][14][15] and other oxyanions [14][15][16][17] that the overall process is 51 Cr (III) 51 Cr(VI) in the heated crystals. [6]) as an indicator of possible 100% transfer of 51 Cr(III) to S1 Cr(VI), the observed Kß/Ka ratio differences of Table 1 have been converted into the fraction of Cr(VI) from the "in situ" analysis.…”
Section: Introductionsupporting
confidence: 89%
“…In each case, the observed ratio increases with a 16 hour thermal pulse at 300°C. These observations are consistent with conclusions from studies of 51 Cr(III)-doped Chromates [10][11][12][13][14][15] and other oxyanions [14][15][16][17] that the overall process is 51 Cr (III) 51 Cr(VI) in the heated crystals. [6]) as an indicator of possible 100% transfer of 51 Cr(III) to S1 Cr(VI), the observed Kß/Ka ratio differences of Table 1 have been converted into the fraction of Cr(VI) from the "in situ" analysis.…”
Section: Introductionsupporting
confidence: 89%
“…The preparation of 51 Cr(III)-doped ammonium Chromate and the method of analysis have been described in a previous paper [3]. The gamma irradiation was made in a 5470 Ci 60 Co 7-source (Gammacell 220, Atomic Energy of Canada) at liquid nitrogen temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Another publication [2] has shown that during isochronal annealing of neutron irradiated ammonium Chromate apart from the increase in 51 Cr(VI) yield considerable changes also occur between the M* and DP forming species. Since analysis of 51 Cr(III)-doped ammonium Chromate [3] has shown that the dopant 51 Cr activity is found not only in M but also in DP form we thought that an investigation of the behavior of the various 51 Cr(III) species during thermal annealing would be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments on the fate of Cr 3+ doping various chromâtes and sulphates submitted to radiation doses have shown the formation of Cr(VI) and polymers of Cr(III). Annealing effects depend on the irradiation temperature [104], The retention of Cr in solid chromium acetylacetone neutron irradiated with the lowest concomitant γ dose is less than 3%. This value agrees quite well with the computed minimum recoil energy of the hot atom.…”
Section: Chromiummentioning
confidence: 99%